Malay Separatist Movement in Southern Thailand: The Rise and Fall of the Gabungan Melayu Patani Raya (GEMPAR), 1948–1949 - Rabiatul Adawiyah Abdullah; Abu Hanifah Haris; Zulkanain Abdul Rahman (International Journal of Asia Pacific Studies, 2026)
Gabungan Melayu Patani Raya (GEMPAR) or the Association of Malays of Greater Patani was established on 1 March 1948 to defend the plight of the Patani Malays and later to champion political ambitions for Patani’s independence from the Thai government. Among its main leaders were Tengku Mahmud Mahyiddeen, Tengku Abdul Kadir Kamaruddin, and Tengku Abdul Jalal bin Tengku Abdul Mutalib. This study examines GEMPAR’s political struggle from 1948 to 1949, highlighting its role in mobilising regional Malay support and advocating for self-determination. This study uses a qualitative approach and library-based research. Primary sources include archival documents from the United Kingdom’s National Archives, such as Colonial Office records, as well as relevant secondary literature, including books, articles, and theses relating to the GEMPAR movement. This study argues that although GEMPAR was short-lived, it played an important role in connecting the Patani Malay nationalist cause with wider post-war Malay political movements. Despite its regional significance, GEMPAR remains largely overlooked in existing scholarship. This study addresses that gap by uncovering its political networks and contributions to Malay solidarity. Studies show that GEMPAR’s struggle had the support of several Malay political organisations, including the Kesatuan Rakyat Indonesia Semenanjung (Peninsular Indonesian People’s Union, KRIS), the Malay Nationalist Party (MNP) or Parti Kebangsaan Melayu Malaya (PKMM), the Kelantan Branch of United Malays National Organization (UMNO), and the Singapore Malay Association.